Effect of Swimming on Gut Microbiota and Inflammation in Colorectal Cancer Cells Transplanted Mice - LI Jiapeng; XIE Qiurong; WEN Ying; CHEN Haichun; PENG Jun; SHEN Aling (康复学报)
ObjectiveTo investigate the effects of swimming on the growth of colorectal cancer (CRC) transplanted tumor in mice, and to explore its regulation mechanism from the perspective of gut microbiota and inflammation.MethodsThe CT-26 bearing mouse model was constructed and the experiment mice were randomly divided into model and swimming groups. The mice in the swimming group were subjected to physical training of swimming for 30 minutes each time and twice per day, 6 days per week for 3 weeks in total. The fresh feces of all mice at 24 hours after the last swimming were collected and stored in liquid nitrogen. The collected tumor tissues were dissected and weighted. The compositions of gut microbiota were analyzed by 16S rRNA sequencing. The functional enrichment of gut microbiota in mice was evaluated by KEGG to compare the differences of metabolic pathways of functional genes in the intestinal flora between the two groups. Enzyme linked immunosorbent assay (ELISA) was used to detect the levels of TNF-α, IL-1β and IL-10 in serum of mice. SPSS 26.0 and GraphPad Prism 7 software were used for statistical analysis.ResultsCompared with the model group, swimming significantly reduced the weight of CRC transplanted tumor in mice (P<0.05). 16S rRNA sequencing and OTU cluster analysis identified 487 overlapping bacterial populations in the model and swimming groups. In addition, 73 unique bacterial populations were found in the model group, while 40 in the swimming group. There was more biodiversity of intestinal flora in the swimming group than that in the model group (P<0.05), with a significant difference in species classification from phylum, class, order, family and genus (P<0.05). The F/B values of Firmicutes and Bacteroidetes decreased in the swimming group, whereas the abundance of butyrate secreting bacteria such as Trichospiraceae increased (P<0.05). Metabolic pathways enrichment of functional genes in the model group was significantly higher than those in the swimming group in terms of infectious diseases, carbohydrate metabolism, parasitism, membrane transport, exogenous biodegradation and metabolism, drug dependence, immune diseases and other amino acid metabolic pathways (P<0.05). As compared with the model group, metabolic pathways of functional genes in the swimming group was significantly enriched in immune system, transportation and storage, biosynthesis of other secondary metabolites, energy metabolism, polysaccharide biosynthesis and metabolism, endocrine and metabolic diseases, nervous system, circulation system and signal molecule interaction pathway, etc. (P<0.05). Compared with the model group, the levels of TNF-α and IL-1β in serum decreased, while that of IL-10 increased in the swimming group (P<0.05).ConclusionRegular swimming could significantly inhibit the growth of CRC transplanted tumors, improve the structural abundance of intestinal flora, and reduce the levels of inflammatory factors in the serum of mice.